Hubungan Panjang Kaki Dengan Kecepatan Lari 100 Meter Siswa Prodi Penjaskesrek Dan Rekreasi Tahun 2020 FKIP - Souhoka, Yacob; Tahapary, Johni Melvin (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2022)
This research is a research carried out by researchers at the Pattimura Ambon University campus. Based on the results of observations made by researchers on students for the 2020 academic year of the Penjaskesrek FKIP Unpatti Ambon during the athletic lecture process the average had short legs, however they were able to keep up with the running speed of other students with longer legs. The aim of this study was to determine whether or not there was a relationship between leg length and 100-meter running speed for students in the 2020 academic year of the Penjaskesrek FKIP Unpatti Ambon Study Program. This research uses quantitative research methods. Taking the problem in this study through direct observation or direct observation in the field. The data collection technique used is the product moment with a sample of 30 or more than 30. The results of the research and discussion of the relationship between leg length and 100-meter running speed for students in the 2020 academic year of the Penjaskesrek FKIP Unpatti Ambon study program are measuring the leg length and continuing with a running test. 100 meters. The research data or raw data is transformed into a new Tscore and then the Tscore data is used for analysis.